Adriamycin-induced podocyte injury via the Sema3A/TRPC5/Rac1 pathway - Liu, Yan; Ge, Ri-Li; Shan, Zhen-Zhen; Wang, Yan-Jun; Yang, Yan-Yan; Sun, Xue; Luo, Peng-Li (Frontiers in Medicine, 2024)
Podocytopathies encompass kidney diseases where direct or indirect podocyte injury leads to proteinuria or nephrotic syndrome. Although Semaphorin3A (Sema3A) is expressed in podocytes and tubular cells in adult mammalian kidneys and has a common effect on the progression of podocyte injury, its mechanism remains unclear. Previous studies have shown increased Sema3A expression in various glomerulopathies, indicating a gap in understanding its role. In this study, analysis of human data revealed a positive correlation between the levels of urinary Sema3A and Podocalyxin (PCX), suggesting a close relationship between Sema3A and podocyte loss. Furthermore, the impact of Adriamycin on podocytes was investigated. Adriamycin induced podocyte migration and apoptosis, along with an increase in Sema3A expression, all of which were ameliorated by the inhibition of Sema3A. Importantly, TRPC5 was found to increase the overexpression of Sema3A in podocytes. A TRPC5 inhibitor, AC1903, alleviated podocyte migration and apoptosis, inhibiting the formation of lamellar pseudopodia in the podocyte cytoskeleton by lowering the expression of Rac1. Furthermore, AC1903 relieved massive albuminuria and foot process effacement in the kidneys of Adriamycin-treated mice in vivo. In conclusion, our findings suggest that Sema3A may impact the cytoskeletal stability of podocytes through TRPC5 ion channels, mediated by Rac1, ultimately leading to foot process effacement. Notably, AC1903 demonstrates the potential to reverse Adriamycin-induced foot process fusion and urine protein. These results contribute to a deeper understanding of the mechanisms involved in podocytopathies and highlight the therapeutic potential of targeting the Sema3A-TRPC5 pathway.